Mineralogy and ore fluid chemistry of the Roc Blanc Ag deposit, Jebilet Hercynian massif, Morocco. (March 2017) - Essarraj, Samira; Boiron, Marie-Christine; Cathelineau, Michel; Tarantola, Alexandre; Leisen, Mathieu; Hibti, Mohamed
Abstract: The Roc Blanc Ag deposit is located about 20 km north of Marrakesh city (Morocco) in the Jebilet Hercynian massif. The ore bodies consist of N-S to NE-SW quartz (±carbonates) veins hosted by the Sarhlef marine sediments. These series, deposited in a Devonian-Carboniferous rift basin context, were deformed during the Hercynian orogeny, and submitted to low-grade regional metamorphism. Two major stages of fluid circulation and metal deposition are distinguished on the basis of mineralogical and paleo-fluid studies carried out on quartz and dolomite (microthermometry, Raman spectroscopy, LA-ICP-MS on individual inclusions, and O, H stable isotope data): (i) an early Fe-As stage, characterized by the circulation of metamorphic aqueous-carbonic fluids, under P-T conditions lower than 200 MPa ± 20 MPa and 400 °C respectively, along N-S structures; (ii) the ore stage, characterized by the circulation of a Na-Mg-K ± Ca high salinity brine, poor in gas but rich in metals such as Fe, Sr, Ba, Zn, Pb, ± Cu (salinity ranging from 19.6 wt% to likely more than 30 wt% NaCl equiv.) and the deposition of a sphalerite/dolomite-calcite assemblage; such a fluid likely evolved to a Na-K-(Ca-Mg)-Ag brine, with significant Pb and Sb concentrations and lower Sr, Ba and Zn concentrations than in the preceding fluid (salinity up to 19.4 wt% NaCl equiv.). The Ag content of the second mineralizing brine ranges from 0.9 mmol/kg to 9.4 mmol/kg solution (100 ppm–1000 ppm), whereas the base metal brine is generally Ag poor (up to 1.3 mmol/kg solution: 140 ppm). Dilution of the Ag brine by low salinity fluids (<6 wt% NaCl equiv., and Th from 130° to 230 °C) seems to be the main driving mechanism for the Ag ore deposition at Roc Blanc, with a possible involvement of cooling and reduction reactions in black schists. Base metal and Ag fluids may have circulated at average temperatures around 200 ± 30 °C or slightly higher and under hydrostatic pressures, along dominant E-W structures. The ore forming model proposed for the Roc Blanc deposit is: (i) the penetration of sedimentary brines coming from the adjacent basins into the basement (i.e. Hercynian formations), where they extracted Ag probably from abundant mafic rocks; ii) the ore deposition in structural traps below the post Hercynian unconformity thanks to brine mixing with low salinity fluids. The fluid circulation probably is related to the Atlasic rifting coeval with the Atlantic Triassic opening. Such a model contrasts with the previous one relating the Roc Blanc to the Hercynian granitic intrusions in the Jebilet. Ag deposition occurred during reworking of the early structures associated with the Hercynian orogenic events and metamorphic fluid circulation which led to the early Fe-As uneconomic stages forming the main N-S quartz veins. Similarities between The Roc Blanc Ag deposit and the major Ag deposits from Anti-Atlas south of Morocco strongly suggest that they resulted from a unique and large fluid circulation event and a major period of metal deposition. Highlights: This study represents a complete characterization of the mineralogy and ore fluid features at the Roc Blanc Ag deposit, Morocco. The Ag concentrations in the mineralizing fluids were determined by a specific calibration of LA-ICP-MS. A metallogenic model was proposed for the Roc Blanc Ag deposit.